2007
DOI: 10.1063/1.2434005
|View full text |Cite
|
Sign up to set email alerts
|

rf magnetron sputter deposition of transparent conducting Nb-doped TiO2 films on SrTiO3

Abstract: rf magnetron sputtering, an established and scalable large area deposition process, is used to deposit Nb:TiO2 and Ta:TiO2 films onto (100) SrTiO3 substrates at temperatures TS ranging from room temperature to 400°C. Optical, electrical, and structural properties similar to those reported for pulsed laser deposition grown films were obtained. In particular, the most conducting Ti0.85Nb0.15O2 films, grown at TS≈375°C, are epitaxially oriented anatase films with conductivity of 3000Scm−1, carrier concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…These results are in good agreement with literature data for TiO 2 :Nb films made by sputtering [15,16]. Furthermore, the resistivity obtained from the analysis of the optical measurements is close to the measured dc value.…”
Section: Electrical Conductivitysupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in good agreement with literature data for TiO 2 :Nb films made by sputtering [15,16]. Furthermore, the resistivity obtained from the analysis of the optical measurements is close to the measured dc value.…”
Section: Electrical Conductivitysupporting
confidence: 81%
“…A recently discovered alternative is doped TiO 2 [3,4], which is different from the other TCOs in that conduction takes place in the d-band rather than in the s-band [5,6]. Earlier work on TCO-type TiO 2 :Nb has employed pulsed laser deposition [3,[7][8][9][10][11][12][13][14], rf magnetron sputtering [15], and dc magnetron sputtering [11,[16][17][18]. The sputtered films were post-treated in H 2 or vacuum at 400 to 600 °C for 1 h, in order to exhibit favorable electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…From the table, one can see that the FWHMs of (0 0 4) peak decrease with increasing substrate temperature, while the intensity of (0 0 4) diffraction increase with increasing substrate temperature. This indicates better c-axis textured anatase NTO films with larger grain sizes are trend to be formed at relatively higher substrate temperatures [9][10][11][12]. As for the film deposited at 998 K, besides the sharp anatase (0 0 4) peak, a small anatase (1 1 2) peak whose intensity decreases with increasing temperature also appears.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, Gillispie et al [9] have reported TNO films deposited on SrTiO 3 substrates by rf sputtering are epitaxially oriented anatase films with resistivity of 3 Â 10 À4 V cm and optical transparency…”
Section: Introductionmentioning
confidence: 99%
“…However, it is considered that the conductivity control is more difficult than the other TCO such as ITO, Sn 2 O and ZnO since d-orbital contributes to forming TiO 2 . Recently, physical vapor deposition such as laser-ablation and reactive sputtering with the post-annealing in reduction ambient have been applied to control the conductivity by using Nb as a donor-dopant and achieved fabrication of highly conductive TiO 2 layer [6] [7]. In the results, it is seemed to be required to enhance the electronic activation of the donor [8], in which Ti 3+ reduced from Ti 4+ probably plays an important role of the conduction in TiO 2 .…”
Section: Introductionmentioning
confidence: 93%